Problematika Literasi Digital Bagi Pemilih Pemula Pada Pilkada 2024 di Kota Sorong - Syaifuddin, Efa Rubawati; Ahriani, Andi; Kahinah, Dwi Iin; Masseni; Abdullah; A’mal Jadid (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2025)
This research examined the digital literacy challenges faced by first-time voters in the 2024 Regional Elections in Sorong City, Southwest Papua. The audience reception analysis method, based on Stuart Hall's Encoding and Decoding theory, was employed to examine the impact of social media on the political information preferences of first-time voters (Generation Z). Furthermore, the study also analyzed the digital literacy challenges faced by Generation Z in the 2024 Regional Elections in Sorong City. Data were collected using observation, interviews, and Focus Group Discussions (FGDs). The study found that Generation Z, who are first-time voters, preferred social media as the source of political information in the 2024 Regional Elections in Sorong City. Instagram and TikTok were the most frequently accessed by Generation Z to obtain information about gubernatorial and mayoral candidates. However, the political participation of first-time voters was still influenced by other factors, such as parents. The digital literacy challenges experienced by first-time voters in Sorong City in the 2024 Regional Elections were promoted by a decline in reading interest, reading long texts, and the preference to use social media as the primary source of political information. Furthermore, the lack of outreach from election organizers, particularly on social media, which is widely accessed by Generation Z, has prevented these first-time voters from fully understanding their role in the 2024 regional elections. The massive exposure to information on social media and the controversies between the candidates have led to a decline in political participation among first-time voters in the 2024 regional elections in Sorong City.